Effect of the deposition strategy on Al-Cu alloy wire+ arc additive manufacture - Ayarkwa, Kwasi Frimpong; Pinter, Zsolt; Eimer, Eloise; Williams, Stewart W.; Ding, Jialuo; Suder, Wojciech (SVR Publishers, 2021)
The effect of the deposition strategy on wire + arc additive manufacture (WAAM) has been conducted for aluminium alloys. In this study, oscillation and parallel deposition strategies were considered for thicker section linear wall building. The results indicate that the deposition strategy has a significant effect on mechanical properties and hardness of the WAAM structure. Optimum ultimate tensile and yield strength were identified after post-deposition heat treatment for both strategies. From microstructure analysis, it was observed that walls produced by oscillation deposition strategy were characterised by equiaxed grains whilst parallel deposited walls were characterised by a mixed grain structure consisting of columnar and equiaxed grains. It was also observed that parallel deposited walls showed an increased number of pores as compared to walls deposited using oscillation strategy. For the studies conducted on aluminium wire + arc additive manufacture, it has been found that the deposition strategy plays an important role in the quality of walls produced
Keywords: Parallel deposition; Oscillated deposition; Aluminium WAAM; Wire + arc additive manufacture; Cold metal transfer